Knowledge services : a strategic framework for the 21st century organization - St. Clair, Guy (Current topics in library and information practice, 2017)
Knowledge services converges information management, knowledge management (KM), and strategic learning into a single enterprise-wide discipline for the benefit of the business or organization in which it is practiced. As the acknowledged framework for strategic knowledge management, knowledge services-the responsibility of the knowledge strategist-leads to excellence in knowledge sharing and ultimately to shaping the organization as a knowledge culture. Knowledge Services: A Strategic Framework for the 21st Century Organization provides guidance for the knowledge strategist and is designed specifically to serve as a reference for that management employee, and for those seeking to become knowledge strategists.